Self-Efficacy and College Readiness of Senior High School Students of a Catholic High School - Herbert T. Martinez; Ma. Wilma M. Maravilla (Philippine Social Science Journal, 2020)
Efficacy beliefs are the foundation of human agency. Beliefs influenced students’ motivation to learn. Students' self-efficacy beliefs could be improved as long as one has a clear idea about the sources of self-efficacy beliefs. Students enable them to grow as self-efficient individuals and overcome problems they face in educational stages or their future life if provided with the opportunity and training on self-efficacy beliefs. Hence, this paper describes the level of efficacy and degree of college readiness of senior high students of a Diocesan Catholic School in Antique during the School Year 2019-2020. Likewise, it explores the significant difference between students’ demographics, self-efficacy, and college readiness. Moreover, it determines the correlation between self-efficacy and college readiness of the students; and whether self-efficacy influenced college readiness.